2019
DOI: 10.1007/s12307-019-00220-6
|View full text |Cite
|
Sign up to set email alerts
|

Altered T Cell Migratory Capacity in the Progression from Barrett Oesophagus to Oesophageal Adenocarcinoma

Abstract: Oesophageal adenocarcinoma (OAC) is an inflammation-driven cancer with poor prognosis and incidence is increasing rapidly. OAC arises from gastro-oesophageal reflux disease (GORD) and reflux-induced Barrett oesophagus (BO). The role of T cells in this disease progression is not yet fully understood. We have previously demonstrated higher proportions of pro-tumour Th2 cells in BO tissue, implicating them in its pathogenesis. While a Th2 immune profile is thought to underlie the metaplastic transformation in BO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Furthermore, NK cell migration toward chemotactic cues in EAC omentum, but not tumor, can be significantly reduced by antagonizing the fractalkine receptor CX3CR1. Importantly, this approach could be used to increase the availability of NK cells for migration toward alternative chemotactic signals in EAC tumor (27). In addition, we have identified that fractalkine induces a conversion from CX3CR1 1 CD27 À to a CX3CR1 À CD27 1 phenotype in NK cells, which is representative of the dominant NK cell phenotype in EAC omentum and is well established as the less cytolytic and predominantly cytokine-producing population (2830).…”
mentioning
confidence: 99%
“…Furthermore, NK cell migration toward chemotactic cues in EAC omentum, but not tumor, can be significantly reduced by antagonizing the fractalkine receptor CX3CR1. Importantly, this approach could be used to increase the availability of NK cells for migration toward alternative chemotactic signals in EAC tumor (27). In addition, we have identified that fractalkine induces a conversion from CX3CR1 1 CD27 À to a CX3CR1 À CD27 1 phenotype in NK cells, which is representative of the dominant NK cell phenotype in EAC omentum and is well established as the less cytolytic and predominantly cytokine-producing population (2830).…”
mentioning
confidence: 99%
“…Despite the immunoregulatory, a potential tumor-promoting action ascribed to such effector T cells, the presence of elevated systemic CCL22 may also indicate uninhibited function of antigen presenting cells, which are important for orchestrating anti-tumor responses and therefore result in a net positive effect when elevated in the periphery. Indeed, previous work by our colleagues has demonstrated that CCL22 expression in EAC tumors is relatively low compared to EAC serum [ 36 ]. Much less is known about the role of CCL26 in cancer, however elevated levels of this chemokine in tumors have been reported in later stage colorectal cancer and has been associated with worse prognosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biopsies were enzymatically digested to perform OGJ cell phenotyping, as previously published [16]. Brie y, tissue was minced using a scalpel and digested in collagenase solution (2 mg/ml of collagenase type IV (Sigma) in Hanks Balanced Saline Solution (GE healthcare) supplemented with 4% (v/v) foetal bovine serum) at 37°C and 1500 rpm on an orbital shaker.…”
Section: Ogj Tumour Tissue Digestionmentioning
confidence: 99%